Pentingnya Efective Communication Dalam Mempersiapkan Calon Pemimpin Di Institut Bisnis Dan Komputer Indonesia - Eva Rianty Angelina Sitanggang; Haposan Seventino Octavianus Hutapea; Antono (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Community service was carried out during the PKKMB (Pengenalan Kehidupan Kampus Mahasiswa Baru) activities for the Academic Year 2024/2025 at Institut Bisnis dan Komputer (IBK) Indonesia. Effective communication is very relevant matery to discuss considering the current life patterns of students who are less concerned about the social environment and this has an impact on the lack of communication with other people around them. The implementation of PKKMB was attended by 159 new students from 4 study programs, namely Accounting Study Program, Computer Science Study Program, Management Science Study Program and Entrepreneurship Study Program. The results of the activity show that new students are aware of the importance of building effective communication and that this will also contribute to their lives when entering the world of work. In the world of work, leadership qualities and the ability to work together in a team are required and this can be achieved by practicing oneself in communicating effectively.